Effects of introduced exotic tree species on Collembola communities: The importance of management techniques - Sousa, J P; Vingada, J V; Barrocas, H; DaGama, M M (PEDOBIOLOGIA, 1997)
Studies of the impact of the substitution of autochthonous forests by plantations of exotic tree species (a quite common phenomenon in Southern European countries) on soil arthropod communities (mainly Collembola and Acarina) generally deal with the effects of the exotic species per se and disregard the management techniques used. In this study the impact of the introduced Eucalyptus globulus on the Collembola communities of Quercus ilex ballota and Quercus suber stands was analysed. Since the autochthonous tree species are similar (in terms of leaf type and the ability to produce litter) the main objective was to examine the effects of the different management techniques used in the two plantations of Eucalyptus. (i) There is a significant difference in management techniques used in the Eucalyptus plantations leading to differences in habitat configuration: the plantation associated with the Helm-Oak stand is used for cellulose paste production, with periodic removal of the shrub and herbaceous layers; the other plantation, close to the Cork-Oak stand, is not managed at all, presenting an abundant shrub layer. (ii) in both cases, the substitution of the Oak species by Eucalyptus caused a disruption of the Collembola communities, although it was more pronounced in e. ilex ballota vs E. globulus (station 1) than in e. suber vs E. globulus (station 2). The number of individuals, the number of taxa and diversity parameters are in most cases greater under Oak species but more evident in station 1. (iii) Given these results, the influence of the factor `'management technique-habitat configuration'' in analysing and interpreting effects of exotics on soil arthropod communities is discussed.
IX International Colloquium on Apterygota, DUBLIN, IRELAND, 1996
Keywords: Collembola community disruption; EUCALYPTUS; Quercus illex; Quercus suber

RUPTURE IN A COLLEMBOLA COMMUNITY STRUCTURE FROM A QUERCUS-ROTUNDIFOLIA LAM FOREST DUE TO THE REAFFORESTATION WITH EUCALYPTUS-GLOBULUS LABILL - Sousa, J P; DaGama, M M (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1994)
Here we compare Collembola populations from a Quercus rotundifolia forest and an Eucalyptus globulus plantation. The overall analysis of data (using both diversity and similarity measures) have shown clear signs of rupture on the structure of collembola populations, with the fauna associated with the Quercus stand being richer (in exclusive and preferential species) and more abundant than the one connected with the Eucalyptus. Data also reflects the faunal stratification between organic and mineral horizons, with the majority of species being associated with upper soil layers in detriment of mineral horizon. These disruptions may be related to profound alterations of habitat characteristics, particularly the frequent removal of shrub vegetation and leaf layer, result of the forestry practices connected with the preparations and management of the eucalyptus plantation.
Keywords: Collembola; EUCALYPTUS; holm-oak; REAFFORESTATION

EFFECTS OF REAFFORESTATION BY EUCALYPTUS-GLOBULUS ON THE EDAPHIC COLLEMBOLA - DaGama, M M; NOGUEIRA, A; DOSSANTOS, AFAM (REVUE D ECOLOGIE ET DE BIOLOGIE DU SOL, 1991)
The authors studied the effects of reafforestation by Eucalyptus globulus on the edaphic Collembola, by means of factorial analysis of correspondences applied to the study of Collembola populations, occurring in coppices of Quercus suber and in Eucalyptus globulus plantations.
Keywords: Collembola; EUCALYPTUS; FACTORIAL; REAFFORESTATION